2012
DOI: 10.1089/ten.tea.2011.0083
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic Factors and Osteoarthritis-Conditioned Medium Inhibit Chondrogenesis of Human Mesenchymal Stem Cells

Abstract: Articular cartilage has a very limited intrinsic repair capacity leading to progressive joint damage. Therapies involving tissue engineering depend on chondrogenic differentiation of progenitor cells. This chondrogenic differentiation will have to survive in a diseased joint. We postulate that catabolic factors in this environment inhibit chondrogenesis of progenitor cells. We investigated the effect of a catabolic environment on chondrogenesis in pellet cultures of human mesenchymal stem cells (hMSCs). We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 30 publications
7
86
1
Order By: Relevance
“…4 In the present study, we investigated the rescue of chondrogenetic differentiation in OA-like conditions by the inhibition of protein kinases. Our studies indicate for the first time that both the JAK inhibitor tofacitinib and the TAK1 inhibitor oxozeaenol can improve chondrogenesis of both fetal and adult hMSCs in the presence of OAS-CM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In the present study, we investigated the rescue of chondrogenetic differentiation in OA-like conditions by the inhibition of protein kinases. Our studies indicate for the first time that both the JAK inhibitor tofacitinib and the TAK1 inhibitor oxozeaenol can improve chondrogenesis of both fetal and adult hMSCs in the presence of OAS-CM.…”
Section: Discussionmentioning
confidence: 99%
“…Krüger et al 3 showed that chondrogenic differentiation of human subchondral progenitor cells is affected by synovial fluid from donors with osteoarthritis (OA) or rheumatoid arthritis (RA). Previously, we have shown that factors secreted by the synovial membrane of OA joints inhibit chondrogenic differentiation of human mesenchymal stem cells (hMSCs), 4 thereby impairing successful tissue engineering. We could not discern a clear relationship between the levels of our primary suspects interleukin-1 (IL-1) and tumor necrosis factor-a (TNF-a) in the osteoarthritic synovium-conditioned medium (OAS-CM) and the strength of inhibition of chondrogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence indicating that proinflammatory cytokines, and particularly IL-1, play an important role in the pathogenesis of OA (17)(18)(19), as well as the inhibition of mesenchymal stem cell (MSC)-based repair of cartilage (20)(21)(22)(23)(24)(25). However, natural inflammatory modulators such as IL-1 receptor antagonist (IL-1Ra) can inhibit IL-1 signaling (26), and studies have shown that biomaterial-mediated delivery of IL-1Ra can mitigate the degradative effects of IL-1 (27).…”
mentioning
confidence: 99%
“…102 In addition to these findings, OA synoviumconditioned medium and synovial fluid have been shown to inhibit MSC chondrogenesis. 103,104 It is evident that modulation of the inflammatory environment in an OA joint is vital to maintain the integrity of engineered cartilage, or achieve efficient cell-based repair.…”
Section: The Effect Of Inflammation On Tissue Engineered Cartilagementioning
confidence: 99%